Phase IB Trial of the Anti-Cancer Stem Cell DLL4-Binding Agent Demcizumab with Pemetrexed and Carboplatin as First-Line Treatment of Metastatic Non-Squamous NSCLC. - McKeage, Mark J.; Kotasek, Dusan; Markman, Ben; Hidalgo, Manuel; Millward, Michael J.; Jameson, Michael B.; Harris, Dean L.; Stagg, Robert J.; Kapoun, Ann M.; Xu, Lu; Hughes, Brett G. M. (Targeted Oncology, 2018)
Background: Delta-like ligand 4-Notch (DLL4-Notch) signaling contributes to the maintenance of chemotherapy-resistant cancer stem cells and tumor vasculature.Objective: This phase IB trial of demcizumab, an IgG2 humanized monoclonal antibody directed against DLL4, was undertaken to determine its maximum tolerated dose, safety, immunogenicity, preliminary efficacy, pharmacokinetics, and pharmacodynamics, combined with standard chemotherapy.Patients and Methods: Forty-six treatment-naive patients with metastatic non-squamous non-small cell lung cancer (NSCLC) were enrolled in this open-label, dose-escalation study using a standard 6 + 6 design. Demcizumab (2.5, 5.0, and 7.5 mg/kg) was given once every 3 weeks with standard doses of pemetrexed and carboplatin using a continuous (six cycles followed by demcizumab maintenance) or a truncated demcizumab regimen (four cycles followed by pemetrexed maintenance).Results: Initially, continuous demcizumab was given until progression but two patients developed grade 3 pulmonary hypertension and congestive heart failure after eight or more infusions. Thereafter, 23 patients were treated with a truncated regimen of demcizumab, which was not associated with any grade 3 or greater cardiopulmonary toxicity. Common adverse events were hypertension, raised brain natriuretic peptide, and those expected from carboplatin and pemetrexed alone. Twenty of 40 evaluable patients (50%) had objective tumor responses. In peripheral blood, demcizumab treatment modulated the expression of genes regulating Notch signaling and angiogenesis, and achieved concentrations exceeding those saturating DLL4 binding.Conclusions: This study has identified a truncated dosing regimen and recommended phase II dose of demcizumab (5 mg/kg q3-weekly ×4) for subsequent clinical evaluation in combination with standard carboplatin and pemetrexed chemotherapy. NCT01189968.